Foliar water uptake and diurnal water recharge-discharge cycle in Pyrrosia piloselloides (L.) M.G.Price (Polypodiaceae) - Nur'ain; Adisyahputra; Reni Indrayanti; Agung Sedayu (Bioma, 2026)
Water availability strongly constrains epiphytic plants, which lack direct access to soil water. To maintain physiological function under these conditions, many epiphytes rely on foliar water uptake (FWU) as a supplementary water source. This study examined FWU capacity and diurnal water dynamics in the epiphytic fern Pyrrosia piloselloides by analysing changes in leaf thickness as a proxy for water recharge and discharge. Leaf thickness was recorded every two hours over 48 hours in nine individuals, and FWU was quantified using seven leaves per individual. FWU increased leaf water content by 0.44–1.37%. Leaf thickness declined during daytime with increasing temperature and decreasing humidity, and increased at night under cooler, more humid conditions. Overall, leaf thickness decreased by approximately 14.11% during the light period. These results demonstrate that P. piloselloides is capable of foliar water uptake and exhibits pronounced diurnal fluctuations in leaf water status, reflecting dynamic ecophysiological responses to environmental variation.